2012
DOI: 10.1155/2012/191879
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation Corrosion and Pitting Corrosion and Their Role in Fatigue Predictive Modeling: State-of-the-Art Review

Abstract: Intergranular attack (IG) and exfoliation corrosion (EC) have a detrimental impact on the structural integrity of aircraft structures of all types. Understanding the mechanisms and methods for dealing with these processes and with corrosion in general has been and is critical to the safety of critical components of aircraft. Discussion of cases where IG attack and exfoliation caused issues in structural integrity in aircraft in operational fleets is presented herein along with a much more detailed pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 106 publications
2
18
0
1
Order By: Relevance
“…The boehmite is nucleated at dislocation centers or pores at the surface of the amorphous oxide film [55]. Then, the boehmite film growth occurs by ionic diffusion through the oxide lattice.…”
Section: Discussionmentioning
confidence: 99%
“…The boehmite is nucleated at dislocation centers or pores at the surface of the amorphous oxide film [55]. Then, the boehmite film growth occurs by ionic diffusion through the oxide lattice.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of many examples of pitting can be explained by the large number of grain boundaries exposed by the pit. The pit initiates intergranular corrosion that progresses into exfoliation and obliterates evidence of the pit [13,14]. Table 1 shows the mechanical properties summary of the tensile specimens cut from the corroded medium scale test panels and the tensile specimens that have undergone the same mechanical processes but have not been exposed to the corrosion environment.…”
Section: Representative Cross Sections Of the Medium Scale Testmentioning
confidence: 99%
“…Corrosion fatigue studies were first reported by Haigh in 1917(Haigh 1917 and followed by McAdam, 1926-1930(McAdam 1926a, b, 1927, 1929. Gough and Sopwith (1932a, b, 1935a, b, 1946a published extensively on it from 1932 to 1946.…”
Section: Scientific Fundamentalsmentioning
confidence: 99%